Sexually dimorphic and radiation dose dependent effect of cranial irradiation on body mass index. Issue 6 (1st December 1999) - Craig, F; Leiper, A D; Stanhope, R; Brain, C; Meller, S T; Nussey, S S
Abstract : OBJECTIVES: To investigate the relation between cranial irradiation received during treatment for childhood leukaemia and obesity at final height. DESIGN: Retrospective cross sectional study. SETTING: Paediatric oncology centres at Great Ormond Street Hospital for Children and the Royal Marsden Hospital. SUBJECTS: Survivors of childhood leukaemia who received cranial irradiation, were in continuous first remission, and had reached final height. An unirradiated group of patients from the United Kingdom acute lymphoblastic leukaemia XI trial was also included; these patients were in continuous first remission and had been followed for at least four years from diagnosis. MAIN OUTCOME MEASURES: Body mass index standard deviation score (BMI z score) at final height for irradiated patients and at most recent follow up for unirradiated patients. Regression analysis was used to examine the effect on BMI z score of sex, age at diagnosis, and the dose of radiation received. RESULTS: For cranially irradiated patients, an increase in the BMI z score at final height was associated with female sex and lower radiation dose, but not with age at diagnosis. Severe obesity, defined as a BMI z score of > 3 at final height, was only present in girls who received 18–20 Gy irradiation and had a prevalence of 8%. Both male and female unirradiated patients had raised BMI z scores at latest follow up and there was no association with age at diagnosis. CONCLUSIONS: These data are further evidence for a sexually dimorphic and dose dependent effect of radiation on the human brain.